Evaluation of phosphorus response to fertilizer placement and hybrid selection - King, Evan W. (Kansas State University, 2013)
Two studies were conducted to evaluate phosphorus response. The first study focused on genetic improvements in corn (Zea mays) for water limited scenarios on phosphorus uptake. The object of the first study was to evaluate plant response to fertilizer and soil phosphorus for contrasting corn hybrids, including a drought tolerant (DT) and conventional hybrid. This study was established at seven locations for two years (2011 and 2012). Four locations were rain fed and three locations were under irrigation. Fertilizer treatments included phosphorus fertilizer at various rates and placements for the two different hybrids. The experimental design randomized complete block with factorial arrangement in four replications. Early growth biomass, early season whole plant tissue concentration (V6), ear leaf tissue concentration, and grain yield was measured throughout the season. Results showed differences in all measurements between hybrids. Differences in most measurements were also significant with fertilizer application. The DT hybrid had less early growth and P uptake but had higher ear leaf P concentration as well as higher yields. The second study focused on P placement, P stratification may be a concern for producers using reduced tillage systems. The objective of this study was to evaluate different placements and rates of P fertilizers in two crops, corn and soybean (Glycine max). This study is currently ongoing; however, here we are presenting data from three locations and four years (2009-2012). Two of the locations were rain fed and one was irrigated. There were four different fertilizer rates with three different placements as well as various combinations of those placements. The experimental design was randomized complete block with four replications at two locations and three replications at one location. Corn early growth biomass, whole plant tissue concentration, ear leaf tissue concentration, soybean uppermost fully open trifoliate P concentration, and yield for both crops were evaluated throughout the season. Results showed response to the phosphorus treatments in all the measured parameters. Results also showed differences in all measured parameters except yield, were significantly affected by placement.
Keywords: Phosphorus; Corn; Soybeans; Agronomy; Agronomy (0285)